2022
DOI: 10.3390/ijms232113057
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Metabolic Pathway in Drought-Stressed Nodules of Faba Bean (Vicia faba L.)

Abstract: Drought is an environmental stress that strongly impacts plants. It affects all stages of growth and induces profound disturbances that influence all cellular functions. Legumes can establish a symbiosis with Rhizobium-type bacteria, whose function is to fix atmospheric nitrogen in organs called nodules and to meet plant nitrogen needs. Symbiotic nitrogen fixation (SNF) is particularly sensitive to drought. We raised the hypothesis that, in drought-stressed nodules, SNF inhibition is partly correlated to hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The Pgbs' substantial overexpression emphasises their relevance in the plant stress response pathway. Phytoglobins have been extensively investigated for their role in plant response to water stress in varied plant species (Hammond et al, 2020;Youssef et al, 2021;Chammakhi et al, 2022). The findings, together with the previous reports, show that OsPgbs overexpression improves tolerance to drought stress.…”
Section: Discussionmentioning
confidence: 77%
“…The Pgbs' substantial overexpression emphasises their relevance in the plant stress response pathway. Phytoglobins have been extensively investigated for their role in plant response to water stress in varied plant species (Hammond et al, 2020;Youssef et al, 2021;Chammakhi et al, 2022). The findings, together with the previous reports, show that OsPgbs overexpression improves tolerance to drought stress.…”
Section: Discussionmentioning
confidence: 77%
“…The localization of NR mRNA within the infected regions of pea root nodules (Kato et al, 2003) and M. truncatula nodule (Horchani et al, 2011) suggest a specific function in this organ. This is supported by the fact that NR activity is required for N 2 fixing symbiosis and nodule energy metabolism (Horchani et al, 2011; Aridhi et al, 2020; Chammakhi et al, 2022). Furthermore, recent study showed a significant increase in the expression of MtNR1 and MtNR2 at 10 hpi, 4 dpi, and 5 wpi, which coincides with a rise in NO levels (Berger et al, 2020a).…”
Section: Discussionmentioning
confidence: 92%
“…Despite the identification of NR mutants in legumes (Feenstra and Jacobsen, 1980; Ryan et al, 1983), no study fully elucidated the significance of these enzymes in the process of nitrogen-fixing symbiosis. Previous works showed that NR activity is required for energy metabolism and N 2 fixation in M. truncatula mature nodule (Horchani et al, 2011; Aridhi et al, 2020; Chammakhi et al, 2022). Recently, Berger et al (Berger et al, 2020a) showed that, during the symbiosis between M. truncatula and Sinorhizobium meliloti , MtNR1 and MtNR2 expression peaks coincide with that of NO production, and that these NO production peaks are abolished by either the use of tungstate, a NR inhibitor, or by a NR1/NR2 RNAi knock-down strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This further reinforces the recurring theme that quantification of soil rhizobia is a useful determinant of BNF potential (Figure 3 ). Decreased BNF can also in part be attributed to hypoxia as a result of compaction of the nodule structure during drought stress, leading to perturbed respiration (Chammakhi et al., 2022 ).…”
Section: Inoculationmentioning
confidence: 99%